2011
DOI: 10.3346/jkms.2011.26.2.258
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C as an Early Biomarker of Nephropathy in Patients with Type 2 Diabetes

Abstract: This study was done to evaluate clinical usefulness of cystatin C levels of serum and urine in predicting renal impairment in normoalbuminuric patients with type 2 diabetes and to evaluate the association between albuminuria and serum/urine cystatin C. Type 2 diabetic patients (n = 332) with normoalbuminuria (n = 210), microalbuminuria (n = 83) and macroalbuminuria (n = 42) were enrolled. Creatinine, urinary albumin levels, serum/urine cystatin C and estimated glomerular filtration rate (eGFR by MDRD [Modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
71
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 23 publications
14
71
1
4
Order By: Relevance
“…This indicates that the association between DN and DR should be close. Studies have found that cystatin C, as a superior marker of GFR, is a sensitive index to find the early phase of DN in patients with diabetes, especially in those diabetic patients with normoalbuminuria [5][6]. One study also found that lower estimated GFR was significantly associated with the severity of DR in Chinese patients with type 2 diabetes mellitus [7].…”
Section: Introductionmentioning
confidence: 85%
“…This indicates that the association between DN and DR should be close. Studies have found that cystatin C, as a superior marker of GFR, is a sensitive index to find the early phase of DN in patients with diabetes, especially in those diabetic patients with normoalbuminuria [5][6]. One study also found that lower estimated GFR was significantly associated with the severity of DR in Chinese patients with type 2 diabetes mellitus [7].…”
Section: Introductionmentioning
confidence: 85%
“…Other markers of DN risk are required for optimal clinical management (9), particularly for patients with T2D who pass through a period of pre-diabetes and may experience renal impairment at the time of diagnosis. In this regard, a number of candidate markers have been proposed for the early identification of renal injury, such as creatinine, kidney enzymes, cystatin C and C-reactive protein (10,11). Genomic regulatory non-coding RNA molecules, namely microRNAs (miRNAs), have been shown to be involved in the control of key biological processes such as proliferation, differentiation, apoptosis and metabolism (12).…”
Section: Introductionmentioning
confidence: 99%
“…NSA2 mRNA copy numbers in patients with and without nephropathy, categorised according to their type of diabetes, are shown in ESM Fig. 1 in serum and urine alongside an increasing degree of albuminuria, being higher in macroalbuminuric patients, and correlates with other risk factors, including GFR, sex, ACR ratio, and C reactive protein [35]. Another biomarker, urinary liver-type fatty acid-binding protein (L-FABP), was found to be elevated in individuals with type 2 diabetes compared with controls, and correlated with blood pressure, HbA 1c , eGFR and cholesterol [36].…”
Section: Discussionmentioning
confidence: 99%